Exploring how augmented reality enriches realistic mathematics education to strengthen students’ understanding of curved-sided geometric ideas - Tri Suranti; Sugeng Sutiarso; Rangga Firdaus (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: Students often find curved-sided geometric shapes difficult to grasp because the material is usually introduced in a highly symbolic way. This condition creates a clear need for learning materials that can present ideas more visually and in contexts that feel relevant to students. Aim: The study seeks to design and examine a learning module that blends Augmented Reality with the principles of Realistic Mathematics Education to support stronger conceptual understanding. Method: Using a Research and Development approach, the study followed the ADDIE sequence from early analysis to final evaluation. The module was reviewed by subject and media experts, tested in a small group to gauge usability, and later implemented in larger classes. Its effectiveness was assessed by comparing posttest scores from a class using the AR–RME module and another class taught with standard materials. Results: Expert feedback showed that both the content and media components reached valid to very valid levels. Students and teachers also reported that the module was easy to use and fit well within classroom activities. The experimental class recorded higher posttest scores than the control group, indicating meaningful gains in conceptual understanding. Conclusion: Augmented Reality, when embedded in a Realistic Mathematics Education setting, offers a learning experience that helps students connect abstract geometric ideas with clearer mental models. The module developed in this study meets the criteria for validity, practicality, and effectiveness, and can serve as a valuable learning resource for geometry instruction.